From Resolution until Social Religious Movement: Effort Eradication of Gambling Activity in Indonesia 1960s-1993 - Mawardi Purbo Sanjoyo (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
Gambling activity is one of the stories in the dynamics history of Indonesia. Its history can be traced from colonial to post-colonial times. In more contemporary times, gambling has even become a kind of commodity that is taken advantage of to cover the shortage of government funds. This habit became a polemic when gambling became a